The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/jb.185.2.592-600.2003
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation ofS-Adenosyl-l-Methionine Enhances Production of Actinorhodin but Inhibits Sporulation inStreptomyces lividansTK23

Abstract: S-Adenosyl-L-methionine synthetase (SAM-s) catalyzes the biosynthesis of SAM from ATP and L-methionine. Despite extensive research with many organisms, its role in Streptomyces sp. remains unclear. In the present study, the putative SAM-s gene was isolated from a spectinomycin producer, Streptomyces spectabilis. The purified protein from the transformed Escherichia coli with the isolated gene synthesized SAM from L-methionine and ATP in vitro, strongly indicating that the isolated gene indeed encoded the SAM-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 39 publications
5
82
0
Order By: Relevance
“…caesius. [199][200][201][202] Although the overall mechanism underlying this activity is not completely understood, the obvious methylation of intermediates leading to the biosynthesis of antibiotics involving SAM provides a strong explanation for the high yield of these compounds. 203 There have been notorious advances in the elucidation of the regulatory mechanisms of antibiotic formation at the biochemical and molecular levels.…”
Section: Strain Improvement By Avoiding or Removing Ccrmentioning
confidence: 99%
“…caesius. [199][200][201][202] Although the overall mechanism underlying this activity is not completely understood, the obvious methylation of intermediates leading to the biosynthesis of antibiotics involving SAM provides a strong explanation for the high yield of these compounds. 203 There have been notorious advances in the elucidation of the regulatory mechanisms of antibiotic formation at the biochemical and molecular levels.…”
Section: Strain Improvement By Avoiding or Removing Ccrmentioning
confidence: 99%
“…riboswitches might be misannotated. Gene regulation of sulfur metabolism is of particular interest in Streptomyces, as SAM levels affect antibiotic production and sporulation in these species (Kim et al 2003;Okamoto et al 2003).…”
Section: Sam-iv Is a Genetic Regulatory Elementmentioning
confidence: 99%
“…Secondary metabolite production in Streptomyces is usually strain specific; thus, it is difficult to develop a universal method to promote the production of secondary metabolites in most Streptomyces strains. 1,2 We observed that increased concentration of S-adenosylmethionine (SAM) by overexpression of SAM synthetase gene stimulated actinorhodin production in Streptomyces lividans, 3,4 and exogenous SAM treatment in culture media enhanced streptomycin production in S. griseus, 5 as well as other secondary metabolite production in many Streptomyces strains. 6 On the basis of these results, we sought to identify SAM-response proteins, which might be targets, to improve secondary metabolite production in many Streptomyces spp.…”
Section: Introductionmentioning
confidence: 99%